Overlooked diversity in Brazilian Cypella (Iridaceae, Iridoideae): four new taxa from the Río de la Plata grasslands - Chauveau, Olivier; Pastori, Tamara; Souza-Chies, Tatiana Teixeira; Eggers, Lilian (Phytotaxa, 2014)
Three new species and one subspecies of Cypella are described for Rio Grande do Sul (RS), Brazil: Cypella altouruguaya from northern RS, C. amplimaculata widely distributed across the state and C. rivularis restricted to southern RS, in grassland streams of the Pampa biome. Cypella hauthalii subsp. minuticristata is found in a central area of Rio Grande do Sul. The different taxa are described, illustrated and compared with related species. The resulting taxonomic framework shows that most of the species described for Cypella occur in the Río de la Plata grasslands, with various infrageneric taxa characterised by a high level of endemism, especially in the Subtropical Grasslands of Southern Brazil.